High-Power, Computer-Controlled, Light-Emitting Diode–Based Light Sources for Fluorescence Imaging and Image-Guided Surgery - Sylvain Gioux; Vida Kianzad; Razvan Ciocan; Sunil Gupta; Rafiou Oketokoun; John V. Frangioni (Molecular Imaging)
Optical imaging requires appropriate light sources. For image-guided surgery, in particular fluorescence-guided surgery, a high fluence rate, a long working distance, computer control, and precise control of wavelength are required. In this article, we describe the development of light-emitting diode (LED)-based light sources that meet these criteria. These light sources are enabled by a compact LED module that includes an integrated linear driver, heat dissipation technology, and real-time temperature monitoring. Measuring only 27 mm wide by 29 mm high and weighing only 14.7 g, each module provides up to 6,500 lx of white (400–650 nm) light and up to 157 mW of filtered fluorescence excitation light while maintaining an operating temperature ≤ 50°C. We also describe software that can be used to design multimodule light housings and an embedded processor that permits computer control and temperature monitoring. With these tools, we constructed a 76-module, sterilizable, three-wavelength surgical light source capable of providing up to 40,000 lx of white light, 4.0 mW/cm 2 of 670 nm near-infrared (NIR) fluorescence excitation light, and 14.0 mW/cm 2 of 760 nm NIR fluorescence excitation light over a 15 cm diameter field of view. Using this light source, we demonstrated NIR fluorescence–guided surgery in a large-animal model.